Searching for the Finance-Growth Nexus in Libya - Cevik, Serhan (IMF Working Papers; Working Paper ;, 2013)
This paper investigates the causal relationship between financial development and economic growth in Libya during the period 1970-2010. The empirical results vary with estimation methodology and model specification, but indicate the lack of long-run relationship between financial intermediation and nonhydrocarbon output growth. The OLS estimation shows that financial development has a statistically significant negative effect on real nonhydrocarbon GDP per capita growth. However, the VAR-based estimations present statistically insignificant results, albeit still attaching a negative coefficient to financial intermediation. It appears that nonhydrocarbon economic activity depends largely on government spending, which is in turn determined by the country's hydrocarbon earnings.